Effects of polycarboxylate superplasticizers on fluidity and early hydration in sulfoaluminate cement system. (20th December 2019) - Tian, Hongwei; Kong, Xiangming; Cui, Yong; Wang, Qibao; Wang, Dongmin
Highlights: The superplasticizer generally used in OPC behaves poorly in SAC. Superplasticizer with high charge density presents decent fluidizing effect in SAC. Adverse ion-bridging effect exists in superplasticizer with low side chain density. Larger carboxylate density of superplasticizer shows stronger retardation effect. Abstract: Three polycarboxylate superplasticizers with varied molecular structure, denoted as PCE4, PCE22 and PCE25 were synthesized by radical copolymerizing acrylic acid (AA) and α-methallyl-ω-hydroxy poly (ethylene glycol) with monomer ratio of 4, 22 and 25 respectively. 2-Acrylamido-2-methylpropane sulfonic acid was used to partly replace AA in basis of PCE22 for preparation of PCE18S4. Flow test and adsorption measurement reveal that the higher charged PCE22 and PCE18S4 exhibit stronger adsorption capability on mineral surfaces and hence better fluidizing effect than the lower charged PCE4. Although PCE25 exhibits sufficient adsorption, its dispersion capability is inferior because of the lower side chain density which leads the polymer prone to be crosslinked by Ca 2+ ions present in pore solution. As shown in the measurements by XRD, BET and calorimetry, the polymers with higher carboxylate content show stronger suppressive effect on ettringite formation and cement hydration and hence perform better in fluidity retention.